COMPARATIVE ANALYSIS OF BANK HEALTH LEVELS USING THE RGEC METHOD AT BANK ACEH SYARIAH AND BANK NTB SYARIAH FOR THE 2020–2024 PERIOD - Jannah, Riadatul; Masruron, Muhammad; Gunawan, M. Indra (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
This study is motivated by the increasing competition among financial institutions in Aceh and West Nusa Tenggara. In the context of national economic development, a sound and stable financial system is a crucial factor that enhances public, customer, and investor confidence. Bank health serves as a key indicator in assessing banking performance and business sustainability. The purpose of this research is to analyze the differences in the health levels of Bank Aceh Syariah and Bank NTB Syariah for the period 2020–2024 using the RGEC method, which covers Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital. This research employs a quantitative approach with a comparative design. The population consists of financial statements and GCG assessment reports published by both banks. The sampling technique used is purposive sampling with two banks as samples, while the data utilized are secondary data. Data analysis was conducted through normality testing, the Mann-Whitney test, and the independent sample t-test. The findings reveal that, in terms of Risk Profile, the NPF ratio shows no significant difference, whereas the FDR ratio indicates a significant difference between the two banks. In GCG, no significant difference is found. In Earnings, the ROA ratio shows no significant difference, while the ROE and BOPO ratios demonstrate significant differences. In Capital, the CAR ratio shows a significant difference. On average, NPF, ROA, and ROE are better in Bank Aceh Syariah, while FDR, BOPO, and CAR are better in Bank NTB Syariah. Overall, Bank Aceh Syariah achieved a composite rating of Very Healthy, while Bank NTB Syariah obtained a composite rating of Healthy.